Rancang Bangun Aplikasi Sistem Pakar Berbasis Android Untuk Mengidentifikasi Hama dan Penyakit Tanaman Padi Pasang Surut - Muhammad Hafiz; Tuti Heiriyani; Rabiatul Wahdah (Agroekotek View, 2019)
One of decreasing factors of rice production are pests and diseases in rice plants (conch, mice, blast, dwarfs). Along the expansion of the tidal field  in South Borneo controled the pest of the rice plants is needs to do  well. To slove farmers' problems, an application was developed to identify pests and rice diseases in the tidal fields by imitating the thinking of a pest and rice plant diseases controller expert to identify a bug or disease and provide a treatment solution. The goal of the study is to create a system that can diagnose pests and diseases of rice plants and analyze the effectiveness of applications to farmers and field agriculture instructor. This study uses the forward chaining method to create an application and in the purposive sampling method with 40 respondents performed in Sub-district Sungai Tabuk in three villages Pamakuan village, Gunung Hirang and Lok Bontar. Results from this study is a system of pest identification and rice disease in tidal fields and the results of the tests of 40 people who responded to 19 chose this application so effective, 20 chose effective,  and 1 chose ineffective. The application testing concludes that the design of the pest and disease identification with expert system on rice plants by forward chaining methods is appropriate as the expect and it is effective to use on farmers.